Microstrip patch antenna design and simulation for S-band wireless applications operating at 3.5 GHz - Rana, Md. Sohel; Fahim, Tahasin Ahmed; Ghosh, Bithe; Rahman, Md. Mostafizur (Institute of Advanced Engineering and Science, 2023)
In the modern world, wireless technology is one way to send information from one place to another. This technology is getting better and better with time, which significantly impacts the activities that make up daily living. This wireless application has the most impact on mobile and other technologies. This research paper shows the design and analysis of a 3.5 GHz microstrip patch antenna (MPA) for wireless applications. The substrate material is Roggers RT/duroid, which has a dielectric permittivity of 2.2 computer simulation technology (CST) software does antenna design and simulation. Some observed parameters are the S-parameter, antenna directivity gain, voltage standing wave ratio (VSWR), and bandwidth. From the simulation, the return loss, VSWR, directivity gain, and bandwidth are -50.4227, 1.0061, 7.43 dBi, and 122.1 MHz respectively. This study aims to find the best return loss, get the most directional gain, and get the VSWR closer to 1. When this antenna was used, the results were better than those in scientific journals and conferences. As a result, this antenna is anticipated to fulfill the requirements of various wireless communication applications effectively.